Caffeine protects against experimental acute pancreatitis by inhibition of inositol 1, 4, 5-trisphosphate receptor-mediated Ca2+ release. Issue 2 (7th December 2015) - Huang, Wei; Cane, Matthew C; Mukherjee, Rajarshi; Szatmary, Peter; Zhang, Xiaoying; Elliott, Victoria; Ouyang, Yulin; Chvanov, Michael; Latawiec, Diane; Wen, Li; Booth, David M; Haynes, Andrea C; et al.
Abstract : Objective: Caffeine reduces toxic Ca 2+ signals in pancreatic acinar cells via inhibition of inositol 1, 4, 5-trisphosphate receptor (IP3 R)-mediated signalling, but effects of other xanthines have not been evaluated, nor effects of xanthines on experimental acute pancreatitis (AP). We have determined effects of caffeine and its xanthine metabolites on pancreatic acinar IP3 R-mediated Ca 2+ signalling and experimental AP. Design: Isolated pancreatic acinar cells were exposed to secretagogues, uncaged IP3 or toxins that induce AP and effects of xanthines, non-xanthine phosphodiesterase (PDE) inhibitors and cyclic adenosine monophosphate and cyclic guanosine monophosphate (cAMP/cGMP) determined. The intracellular cytosolic calcium concentration ([Ca 2+ ]C ), mitochondrial depolarisation and necrosis were assessed by confocal microscopy. Effects of xanthines were evaluated in caerulein-induced AP (CER-AP), taurolithocholic acid 3-sulfate-induced AP (TLCS-AP) or palmitoleic acid plus ethanol-induced AP (fatty acid ethyl ester AP (FAEE-AP)). Serum xanthines were measured by liquid chromatography-mass spectrometry. Results: Caffeine, dimethylxanthines and non-xanthine PDE inhibitors blocked IP3 -mediated Ca 2+ oscillations, while monomethylxanthines had little effect. Caffeine and dimethylxanthines inhibited uncaged IP3 -induced Ca 2+ rises, toxin-induced Ca 2+ release, mitochondrial depolarisation and necrotic cell death pathway activation; cAMP/cGMP did not inhibit toxin-induced Ca 2+ rises. Caffeine significantly ameliorated CER-AP with most effect at 25 mg/kg (seven injections hourly); paraxanthine or theophylline did not. Caffeine at 25 mg/kg significantly ameliorated TLCS-AP and FAEE-AP. Mean total serum levels of dimethylxanthines and trimethylxanthines peaked at >2 mM with 25 mg/kg caffeine but at <100 µM with 25 mg/kg paraxanthine or theophylline. Conclusions: Caffeine and its dimethylxanthine metabolites reduced pathological IP3 R-mediated pancreatic acinar Ca 2+ signals but only caffeine ameliorated experimental AP. Caffeine is a suitable starting point for medicinal chemistry.